Which Firms Follow the Market? An Analysis of Corporate Investment Decisions - Bakke, Tor-Erik; Whited, Toni M. (Review of Financial Studies, 2010)
[We test whether stock market mispricing or private investor information in stock prices affects corporate investment. We develop an econometric methodology that disentangles stock-price movements that are relevant for investment from those that are not. We combine this decomposition with proxies for private information and mispricing to devise unbiased tests for the effects of mispricing and information on investment. We depart from much of the literature by finding that stock market mispricing does not affect investment, especially that of large firms and firms subject to mispricing. In contrast, we confirm previous evidence that managers incorporate private investor information when making investment decisions.]